2022
DOI: 10.3389/fenvs.2022.955982
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial-Temporal Evolution Characteristics and Driving Factors of the Green Utilization Efficiency of Urban Land in China

Abstract: With the acceleration of urbanization, the urban land area of different spatial scales in China continues to increase, the urban land use efficiency is relatively low, and there are great regional differences. Land is an important material carrier for human production, life, and socio-economic activities. Reasonable measurement of the green utilization efficiency of urban land (Glande) has important theoretical and practical significance for the realization of urban land green use and the formulation of relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It has been confirmed that under the constraint of considering traditional industrial pollution, there was a certain spatial spillover effect of the influencing factors of ULGUE [37,40]. The traditional regression models do not consider spatial correlations [80].…”
Section: Spatial Durbin Model (Sdm)mentioning
confidence: 90%
See 2 more Smart Citations
“…It has been confirmed that under the constraint of considering traditional industrial pollution, there was a certain spatial spillover effect of the influencing factors of ULGUE [37,40]. The traditional regression models do not consider spatial correlations [80].…”
Section: Spatial Durbin Model (Sdm)mentioning
confidence: 90%
“…The choice of indicators for an urban capital stock indicates capital inputs and is relatively consistent. In the measurement of the economic output of urban land, most studies have chosen municipal GDP or secondary and tertiary industry GDP [37]. The selection of green space coverage and green space area is more common in the desired environmental output [38].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Land supports social development; its uses reflect an economy’s production scale and technological efficiency, and it determines the material environmental conditions of human life [ 21 ]. In recent years, it has been widely recognized that urban land use should not be limited to pursuing economic benefits but should include the environmental benefits generated by land use [ 8 ]. Green development and environmental governance cannot be separated from legal protection [ 22 ].…”
Section: Institutional Background and Hypothesis Developmentmentioning
confidence: 99%
“…It is worth noting that although there were differences in various measurement methods, environmental pollution generated in the process of land use was regarded as an undesirable output. In terms of spatial–temporal pattern and dynamic evolution characteristics, based on the objective facts of regional differences in industrial policies and resource endowments, existing studies discussed the spatial–temporal pattern 22 , 28 , spatial correlation 26 , spatial agglomeration characteristics 20 , 28 and spatial heterogeneity 21 , 29 of the green use efficiency of urban land, the main purpose of this research is to grasp and predict the change trend of the green use efficiency of urban land. In terms of influencing factors, scholars investigated the impact of urban agglomeration construction 30 , smart city construction 23 , multi-center development 19 , economic development level and industrial structure upgrading 28 , 31 , land finance 32 , location-oriented policies 33 , low-carbon city pilot policies 34 , 35 , new urbanization 24 and other factors on the green use efficiency of urban land, the exploration of driving factors and hindering factors provides a reasonable solution for promoting improvement of GEUCL.…”
Section: Introductionmentioning
confidence: 99%